Exploration of challenges faced by Grade 9 educators in the implementation of outcomes-based education (OBE) in Maleboho East Circuit of the Limpopo Province Department of Education - Moganwa, Lesiba Samuel (My University, 2007)
This study sets out to explore the challenges faced by grade 9 educators in the implementation of Outcomes-Based Education (OBE) in Maleboho East Circuit in Limpopo Province in view of the role played by this new education approach in the government’s agenda for social transformation. The study is mainly exploratory in design and has been undertaken within a qualitative framework. Thus, the study does not purport to come with explanations of cause and effect relations. It only explores the challenges that impact on successful implementation of the OBE approach. The research results show that the OBE approach is not effectively implemented in schools, due to inadequate teacher training, limited or little support to educators in their classroom practice, overcrowded classes and poor working conditions of educators. There is a need for a multi-dimensional approach that aims to address not only deficiencies in training, but also to impact on the attitudinal changes of educators.
Thesis (M.Dev.) --University of Limpopo, 2007.
Keywords: Outcomes-Based Education; 373.01109; Competency based education - South Africa